Flow analysis and optimization of a vertical axis wind turbine blade with a dimple. Issue 1 (1st January 2021) - Yoo, Seungwoo; Oh, Sahuck
Abstract : In this study, the influences of the geometric characteristics of a dimple on the aerodynamic properties of a vertical axis wind turbine are investigated, and its configuration optimization that maximizes the wind turbine's performance is carried out. Three parameters that control the position, size and depth of the dimple are used to parameterize the dimple's configuration and to conduct optimization. With these parameters, when the flows around the wind turbines with various dimples are compared, several meaningful physical phenomena are found. First, a strong association between the position of a dimple and the power coefficient is found where the power coefficient increases as the position of the dimple approaches the trailing edge of the wind turbine blade. Second, high-performance enhancement tends to be achieved when a dimple is small, but this attribution becomes weaker as the dimple moves toward the trailing edge. Furthermore, when the flow of the optimal wind turbine is compared with the one without a dimple, a reduction of the blade wake and delay of the flow separation can be identified. Finally, the shed vortices from the optimal wind turbine blade are weaker and decay faster than the ones shed from the wind turbine without a dimple.